A influência da percepção de atributos sustentáveis nas atitudes e intenções do comprador organizacional - Becker, Fábio Ricardo (Universidade do Vale do Rio dos Sinos, 2016)
The reduction of consumption and production levels has been one of the highlighted ways to mitigate climate change, therefore allows reducing the use of natural resources and fossil fuels, as well as reduction of other environmental and social impacts. This paper addresses the organizational buyer behavior, for it evaluates through two experimental studies the perception of the buyer for products developed with sustainable attributes from ecodesign strategies. The first study involved a sample of 139 students and in the second study sample was 52 buyers. The procedures and methods used followed the approach of conjoint analysis as research methods. The experiments were modeled considering the attributes and their levels for the projection of the stimuli (product profiles), and also consider ecological awareness and purchase intention in organizational buyer. The results show that environmental concerns, price, product durability and its efficiency in energy consumption can influence the buying decision, since benefits are perceived as cost reduction and better use of resources.
Keywords: Ecodesign; Compra organizacional; Intenção de compra; Análise conjunta; Sustentabilidade; Organizational buying; Buy intention; Conjoint analysis; Sustainability; ACCNPQ::Ciências Sociais Aplicadas::Administração